Draft Annual Plan 1987-88, Government of Rajasthan - Planning Commission (Planning Commission, 1987)
The proposals for Annual Plan 1987-88 have been framed keeping in view the objectives enunciated in the Seventh Five year Plan Document as also the overall position of the state, taking stock of the physical progress made in different key sectors, giving due importance to renewed 20-point programme and in conformity with the guidelines contained in Planning Commission’s D.O. letter no. PC (P)2/86 dated 21.8.86. The level of expenditure expected to be reached by the end of 1986-87 as also the target levels stipulated under various sectors in Seventh Five Year Plan have been kept into consideration. Priority has been given to the on-going major projects under Irrigation & Power sectors, such as IGNP, Mahi Bajaj Sagar, Medium Irrigation Projects, Kota Thermal etc. so as to ensure their early completion for achieving early benefits without further cost overrun. Likewise, sectors/programmes covered under 20-point programme and the Minimum Needs Programme basically intended for the amelioration of the economic conditions of weaker sections of society have also been given due priority and adequately provided.
Draft Annual Plan 1987-88
Government of Rajasthan